Economic Empowerment of PKK Women in Improving Community Welfare in Pasir Endah Village, Ujungberung City District - Yeti Rohayati; Tati Sarihati; Ira Adriati; Shinta Dzauharoh (TGO Journal of Community Development, 2024)
This Community Service activity aims to help PKK mothers in Pasir Endah Village, Ujungberung District, Bandung City in making Jumputan batik with the aim of providing understanding in improving family welfare. The activity was carried out in the form of direct practice in making jumputan batik which was attended by approximately 30 residents of Pasir Endah sub-district, Ujung Berung District, Bandung City. Through this activity, it is hoped that it will provide benefits in that the women of PKK Pasir Endah, Ujung Berung District, Bandung City will have the skills to make jumputan batik so that they can improve the welfare of their families. Apart from that, it is hoped that PKK women will get an idea of how to form an MSME business which can be done after identifying and inventorying the potential of the artistic works owned by PKK women so that they can be developed to be more economically productive and they can also understand alternatives in carrying out efforts to find sources of funding by the aim of improving family welfare.